Tracking legacy radionuclides in St. Louis, Missouri, via unsupported 210Pb. (March 2016) - Kaltofen, Marco P.J.; Alvarez, Robert; Hixson, Lucas
Abstract: Analysis of 287 soil, sediment and house dust samples collected in a 200 km 2 -zone in northern St. Louis County, Missouri, establish that offsite migration of radiological contaminants from Manhattan Project-era uranium processing wastes has occurred in this populated area. Specifically, 48% of samples (111 of a subset of 229 soils and sediments tested) had 210 Pb concentrations above the risk-based soil cleanup limits for residential farming established by the US Department of Energy at the Fernald, OH, uranium plant, which handled and stored the same concentrated Manhattan Project-era wastes; the geographical distribution of the exceedances are consistent with water and radon gas releases from a landfill and related sites used to store and dispose of legacy uranium wastes; and offsite soil and house dust samples proximal to the landfill showed distinctive secular disequilibrium among uranium and its progeny indicative of uranium ore processing wastes. The secular disequilibrium of uranium progeny in the environment provides an important method for distinguishing natural uranium from industrial uranium wastes. In this study, the detection of unsupported 210 Pb beyond expected atmospheric deposition rates is examined as a possible indicator of excessive radon emissions from buried uranium and radium-containing wastes. Highlights: We sampled and analyzed 287 urban soils and sediments for uranium processing wastes. Radium and unsupported 210 Pb were the primary tracers for wastes. The goal was to track Manhattan Project wastes around St. Louis, MO. Activity levels in the environment peaked around land disposal sites. Unsupported 210 Pb and isotopic uranium & thorium were also found in house dusts.